Reserve of carbon in a silvopastoral system composed of Pinus patula and native herbaceous - Oliva, Manuel (2017)
The objective of the research was to determine the carbon reserve retained under a silvopastoral system with Pinus patula, located in Amazonas, Peru. For the carbon estimation, 06 plants were used by the direct method, the shafts were sectioned every 2 meters and from these were obtained samples of 5 cm of thickness prior to the total weighing. For the branches and leaves the total weight was weighed and samples of 200 g were selected. For the collection of leaf litter and native herbaceous samples, the quadrant method was used and soil samples were collected around each plant. The data were obtained through the formulation of allometric equations and selection of the highest correlation estimated, based on variables such as diameter at chest height (DAP) and height of the stem (AF). As a result, 92.13 t / ha of stored carbon and 337.20 t / ha of carbon equivalent were found. In addition, the research allowed to establish an equation that allows estimating the amount of carbon and CO2 in the pine tree: Dry biomass = 0.6575 * DAP1,1794 (r2 = 0.91).